-x+35=-6x-3x

Simple and best practice solution for -x+35=-6x-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+35=-6x-3x equation:



-x+35=-6x-3x
We move all terms to the left:
-x+35-(-6x-3x)=0
We add all the numbers together, and all the variables
-x-(-9x)+35=0
We add all the numbers together, and all the variables
-1x-(-9x)+35=0
We get rid of parentheses
-1x+9x+35=0
We add all the numbers together, and all the variables
8x+35=0
We move all terms containing x to the left, all other terms to the right
8x=-35
x=-35/8
x=-4+3/8

See similar equations:

| 20x+153=9x | | 14=11+8/w.6 | | 8q-63=17 | | s-62/6=6 | | 11=4x−3 | | 3(u+5)=18 | | 3y+6y+4y-7=-8 | | 29=b-5 | | 90=x+(58+3x) | | 55=v+31 | | 7=21-2p | | 99=48+c | | m/9-12=21 | | e-1/3=3/5 | | 54=8w-10 | | 64=13+z | | 108=-12-4(5n+7 | | 3y=7y-1 | | 10=j-60/2 | | 7(x-6)-4=7 | | x/7=5=-1 | | 5x^2-16x+13=105x2−16x+13=10 | | 2x-6+7x+4=180 | | 86v=86 | | 91=7(t-75) | | v/2+9=12 | | w+8/4=5 | | 52=j-44 | | 23-3g=5 | | 92=23b | | 2y4,+3=11 | | 3x-3.7=2.3 |

Equations solver categories